2019
DOI: 10.1002/csp2.9
|View full text |Cite
|
Sign up to set email alerts
|

Ecological and social consequences of bison reintroduction in Colorado

Abstract: Bison were instrumental in shaping North America's Great Plains. Interest in restoring this iconic species and their ecological role in grassland ecosystems is rapidly gaining momentum. To evaluate the potential for bison to enhance habitat quality for wildlife and catalyze public engagement in grassland conservation, we assessed both the ecological and social effects of a recent bison reintroduction (2015) to northern Colorado. Specifically, we explored the effect of bison reintroduction on: (a) bird density … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Our study takes place in locations where bison grazing effects have been present on the landscape for many decades. But Wilkins et al (2019) did not find any changes in bird density 2 years after bison reintroduction in a shortgrass prairie system. McMillan et al (2019) found mixed support for vegetation changes that could influence grassland songbird community responses 10 years after bison reintroduction in a mixed‐grass system.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Our study takes place in locations where bison grazing effects have been present on the landscape for many decades. But Wilkins et al (2019) did not find any changes in bird density 2 years after bison reintroduction in a shortgrass prairie system. McMillan et al (2019) found mixed support for vegetation changes that could influence grassland songbird community responses 10 years after bison reintroduction in a mixed‐grass system.…”
Section: Discussionmentioning
confidence: 90%
“…There is substantial interest in reintroducing bison on the landscape (Fuhlendorf et al, 2018; Sanderson et al, 2008). Thus, understanding the role of bison as conduits of environmental modification is increasingly important to integrate their ecological effects into grassland songbird conservation efforts (McMillan et al, 2019; Wilkins et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Although understudied, evidence suggests that reintroductions have the potential to (re)establish important socio‐cultural connections between people, wildlife and landscapes (e.g. Lindon & Root‐Bernstein, 2015; Wilkins et al, 2019). Auster, Barr, et al (2020) suggest that positive emotions generated by seeing certain reintroduced species or signs of their presence could lead to mental health benefits.…”
Section: Discussionmentioning
confidence: 99%
“…In New Zealand there has been a large increase in the number of community-led projects that can result in wider engagement and interest in environmental issues (Department of Conservation, 2012). The reintroduction of bison Bison bison to North America's Great Plains was found to have immediate positive benefits on visitors and in connecting people to conservation (Wilkins et al, 2019). There can be direct economic benefits too; for example £4.9 to £8 million of annual tourist spend on the Isle of Mull in Scotland results from people wishing to see the white-tailed eagles that resulted from reintroduction (Morling, 2022).…”
Section: Addressing the Risks And Opportunities For Peoplementioning
confidence: 99%